Respostas
respondido por:
1
Primeiro vamos fatorar o que der pra fatorar:
8 | 2
4 | 2
2 | 2
1
E embaixo:
18 | 2
9 | 3
3 | 3
1
Montando a expressão:
8 | 2
4 | 2
2 | 2
1
E embaixo:
18 | 2
9 | 3
3 | 3
1
Montando a expressão:
respondido por:
0
________ _____ _____
√6 + ∛8 = √6 + ∛2³ = √6 + 2 = √8 = 2√2 = 2
√18 √18 √18 √18 3√2 3
Resp.: 2
3
Decompor:
18 : 2
9 : 3
3 : 3
1 = 3².2 = √9.√2 = 3√2
8: 2
4: 2
2: 2
1 = 2.2.2 = √4.√2 = 2√2
√6 + ∛8 = √6 + ∛2³ = √6 + 2 = √8 = 2√2 = 2
√18 √18 √18 √18 3√2 3
Resp.: 2
3
Decompor:
18 : 2
9 : 3
3 : 3
1 = 3².2 = √9.√2 = 3√2
8: 2
4: 2
2: 2
1 = 2.2.2 = √4.√2 = 2√2
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás